Achieving chronic hepatitis B functional cure: Factors and potential mechanisms - Jiarui Zheng; Zilong Wang; Linxiang Huang; Zixuan Qiu; Yandi Xie; Suzhen Jiang; Bo Feng (Virus Research)
Chronic hepatitis B (CHB) is a significant global health issue affecting approximately 254 million individuals worldwide. Achieving the loss of hepatitis B surface antigen (HBsAg), either with or without seroconversion to hepatitis B surface antibody (HBsAb), is regarded as a functional cure and the optimal goal for addressing CHB, and can be achieved through various approaches, including induction with nucleos(t)ide analogues (NAs), induction with pegylated interferon alpha (PegIFNα), and spontaneous clearance of HBsAg. Spontaneous clearance of HBsAg is rare, while NAs can directly inhibit HBV DNA, they are unable to act on covalently closed circular DNA (cccDNA), hence inhibiting HBsAg production or clearing HBsAg is extremely challenging. On the other hand, functional cure based on PegIFNα shows good long-term durability, but over 10 % of patients still experience relapse, mostly within 48 weeks after functional cure. Factors related to CHB functional cure with antiviral therapy are complex, including host factors, viral factors, environmental factors, etc. The integration of HBV DNA into liver cells, persistence of HBV cccDNA, insufficient B cell responses and compromised T cell function pose significant barriers to HBV clearance. Therefore, this study systematically reviewed the relevant factors and potential mechanisms influencing functional cure CHB, which can provide a basis for personalized treatment, help predict treatment outcomes and assess prognosis, and provide theoretical support for the advancement of novel treatment strategies and medications.